Validitas LKS berbasis problem solving untuk mencapai keterampilan 4C pada materi suhu kalor dan teori kinetik gas kelas XI SMA/MA - Rara Nur Rida M.Y; Yenni - Darvina; Syafriani - -; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2019)
Communication skill, collaboration, critical thinking is a demand in education of this 21th century, because these skills are needed by student to compote against global competition, so that the education is a top priority in realizing high-skilled students. In order to have these skills, teacher can use learning models that support students in achieving 4C skills that are assisted by a learning device. It is not easy to achieve these skills, especially in learning physics. Student could only understand the formula but their ability in the process of problem solving and determining the use of formula appropriately was still low. This was because students were still fixated on the sample questions which was given by the teacher. Researcher are interested in creating a product based on problem solving syntaxes in which each syntax integrates4C skills. This study aims to produce a valid and practical worksheet to use. The type of research used in this study is the type of research and development (R&D). This study was validated. Based on the research that has been done, the resulting product is a problem solving based worksheet to achieve 4C skills in the heat temperature material and the kinetic theory of gas class XI SMA / MA. The products that have been made are validated by experts. The results obtained from the assessment, the product has an average value of validity of 87,2% with a very valid, This shows that LKS is feasible to be used in the learning process. So that it can help and make it easier for the teachers in achieving the demands of 21st-century education.